Novel evidence on the determinants of the global burden of hunger - CGIAR Research Program on Rice (2021)
Our study provides evidence that policy makers can use as a proof of concept to prioritize (i) enhancement of micronutrient density of cereals; (ii) diversification of production systems and consumer diets; and (iii) development of nutrition-sensitive food value chains.